PENERAPAN TUGAS POKOK LEGIUN VETERAN REPUBLIK INDONESIA DEWAN PIMPINAN DAERAH PROVINSI RIAU - Yani A, Fitri; Oemar, Kamaruddin; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: As a form of running the Obligations and Responsibilities as a Veteran of the Republic of Indonesia, Veterans have several Main Tasks, either individually run (Veteran) or together in a veterans organization (LVRI). The Veterans Organization (LVRI) located in each Region or Province is led by the LVRI Regional Leadership Council, such as the Board of Regional Leaders of Riau Province LVRI today. The Headquarters of Riau Province LVRI established since 1973. In counteracting the teachings / teachings contrary to Pancasila DPD LVRI Riau Province continues to inherit the spirit spirit and values kejuangan 45 and provide guidance to the Veterans related activities. In order to improve the Veterans' Welfare of Riau Province, Colonel. Retired. Himron Saheman as chairman of DPD LVRI Riau province Period 1992-2013 with Riau governor H. Arifin Achmad seeks the construction of Bhaskara Purna Yudha in 1973 as the Headquarters of LVRI Riau Province and seeks the Development of the Happy Tombs of Kusuma Bhakti Warriors with the governor of Riau May. Jen. Retired. Suripto. to give special education priority for Veterans' children, Colonel. Inf. Wirasmo as chairman of the DPD LVRI period 1970-1973 established ITTR Vocational Education (English, Telegraph, Radio Engineering) with other Veterans member Julier Joni Djakamsi.Keywords: Veteran, LVRI, Main Task, Riau Province